Lignin to Materials: A Focused Review on Recent Novel Lignin Applications - Yu, Osbert; Kim, Kwang Ho (MDPI, 2020)
In recent decades, advancements in lignin application include the synthesis of polymers, dyes, adhesives and fertilizers. There has recently been a shift from perceiving lignin as a waste product to viewing lignin as a potential raw material for valuable products. More recently, considerable attention has been placed in sectors, like the medical, electrochemical, and polymer sectors, where lignin can be significantly valorized. Despite some technical challenges in lignin recovery and depolymerization, lignin is viewed as a promising material due to it being biocompatible, cheap, and abundant in nature. In the medical sector, lignins can be used as wound dressings, pharmaceuticals, and drug delivery materials. They can also be used for electrochemical energy materials and 3D printing lignin-plastic composite materials. This review covers the recent research progress in lignin valorization, specifically focusing on medical, electrochemical, and 3D printing applications. The technoeconomic assessment of lignin application is also discussed.
Keywords: GRAPHENE QUANTUM DOTS; LIGNOCELLULOSIC BIOMASS; SUGARCANE BAGASSE; DRUG-DELIVERY; PERFORMANCE; POLYMER; SEPARATION; HYDROGELS; NANOPARTICLES; PRETREATMENT